Adolescent and young adult-friendly primary health care services in low- and middle-income countries: a scoping review - Retno Asti Werdhani; Dessie Wanda; Husain Muhammad Fajar Surasno; Mariska Anindhita; Vican Sefiany Koloi; Fitriana Murriya Ekawati; Indah Suci Widyahening; Lena A. Sanci (Discover Social Science and Health)
Abstract Introduction A comprehensive and innovative adolescent health care program focusing on adolescent health problems in low- and middle-income countries (LMICs) is lacking. We reviewed the research literature on models for adolescent and young adult (AYA)-friendly primary healthcare services (LMICs). Methods and analysis This scoping review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Review. The PubMed, Embase, and Scopus databases were searched. The data were screened with COVIDENCE software® and extracted thematically. Results Together, the search generated 1101 articles, 40 of which met the inclusion criteria. The significant domains identified for AYA-friendly healthcare care services in LMICs were health facilities, health literacy, and the environment and empowerment, which were derived from eight themes, namely, appropriate package of services, facility characteristics, data and quality improvement, providers’ competencies, adolescent health literacy, equity and nondiscrimination, community support, and adolescent participation. Conclusion The friendly primary health care services model in LMICs should pay attention to health facilities, literacy, and environmental support. The identified domains provide insight for advising and implementing primary healthcare services that provide a trusted, holistic, comprehensive, integrated, and ongoing health service to AYA, thereby closing the gap in healthcare services for AYA.